Home Activity-based Interventions for the Neurologically Impaired Upper Extremity: A Scoping Review. Issue 2 (May 2021) - Bell, Alison; Grampurohit, Namrata; Marino, Ralph J.; Duff, Susan; Kaplan, Gary; Calhoun Thielen, Christina; Mulcahey, M.J.
Background: Activity-based therapy (ABT) for the upper extremity (UE) enables neurologic recovery with tasks that are functional, intense, and highly repetitive. A large proportion of rehabilitation occurs in the home and there is a gap in literature on the application of ABT within the home. The objective of this scoping review was to describe ABT in the home-setting for the neurologically-impaired UE. Methods: A systematic scoping review included searches of: MEDLINE, CINAHL, Cochrane, and OTSeeker. Results: A systematic search yielded 51 final studies. About 61% of ABT studies were exclusively within the home, others included outpatient visits (37%). Telerehabilitation was used in 37% of the studies with live-video and store forward techniques equally represented. ABT supported by technology was used in 61% of studies. Dosing of intervention ranged from 7 to 120 hours, with a mean of 34.5 hours of practice. Adherence with intended dosing was reported in 27% of studies and subjects completed a mean of 86% of the intended practice time. Sixty-seven percent of studies reported some degree of practice without therapist supervision. Conclusions: The results showed wide variability in the intervention methods, dosing and technology used in homebased settings. The high rate of adherence with dosing is encouraging for the application of homebased neurologic UE interventions. This scoping review highlights feasibility of UE ABT within the home and need for further research.